Synthesis of low-density polyethylene derived carbon nanotubes for activation of persulfate and degradation of water organic micropollutants in continuous mode - Rui S. Ribeiro (2022)
Plastic derived carbon nanotubes (CNTs) were tested as catalysts in persulfate activation for the first time. Four catalysts were prepared by wetness impregnation and co-precipitation (using Al2O3, Ni, Fe and/or Al) and implemented to grow CNTs by chemical vapour deposition (CVD) using low-density polyethylene (LDPE) as carbon feedstock. A catalyst screening was performed in batch mode and the best performing CNTs (CNT@Ni+Fe/Al2O3-cp) led to a high venlafaxine mass removal rate (3.17 mg g-1 h-1) in ultrapure water after 90 min (even with a mixture of micropollutants). Its degradation increased when the matrix was replaced by drinking water and negligibly affected in surface water. A composite polymeric membrane was then fabricated with CNT@Ni+Fe/Al2O3-cp and polyvinylidene fluoride (PVDF), a high venlafaxine mass removal rate in surface water being also observed in 24 h of continuous operation. Therefore, the results herein reported open a window of opportunity for the valorisation of plastic wastes in this catalytic application performed in continuous mode.